SISTEM DINAMIS KETERSEDIAAN DAGING AYAM RAS PEDAGING (BROILER) DI PROVINSI BALI - Surya Atmaja, I Putu; Satriawan, I Ketut; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): Juni, 2019)
The demand of broilers meats in Bali Province are very high and more dominated from hotels, restaurants, cafes and industrial. The aims of this research are to establish the factors those influenced the availability broiler meat, to arrange dynamic system modeling broiler meat availability, calculate the availability policy for fulfilling the need of animal protein, to arrange alternative recommendation of scenario policy for fulfilling the demand of broiler meat in Bali Province. Simulation are conducted over a period of 10 years, starting from 2012 until 2021. The factors those influenced the availability broiler meat in Bali Province are broiler meat production and broiler meat requirements . The simulation result showed that the production of broilers meat in Bali Province did not afforded to fulfil the demands of broilers since 2012. The avaibilty of broilers in Bali Province mostly appointed the reduction from the bigining to the end of the simulation year. According to the simulation result several scenarios, the policy which was very effective and possible to be developed for fulfilling the demand of broilers meat is by adding the weight of broilers during the livestock and also by adding more chicken. Key words : system dynamics, availability, broiler meat , simulation s